Productivity of Pinus caribaea VAR. hondurensis and its relations with chemical attributes of soils in the brazilian Cerrado region - Silva, Vinicius Evangelista; Teodoro da Silva, Paulo Ricardo [UNESP]; Montanari, Rafael [UNESP]; Silva Lisboa, Sara Dias da [UNESP]; Bellati Batello, Edmar Roberto [UNESP]; Aguilar, Jailson Vieira [UNESP]; Manzani Lisboa, Lucas Aparecido [UNESP]; Albertini, Marlon Marino [UNESP] (Centro Pesquisas Florestais, Ufsm, 2019)
Forestry with exotic species plays an important socioeconomic role in Brazil, providing raw material for the production of wood, firewood, charcoal, cellulose, among others. In this sense, it becomes necessary to deepen the knowledge about the environmental variables that control the productivity of Pinus, especially the edaphic ones. The objective of the present work was to evaluate the spatial variability of soil and plant chemical attributes in a commercial plantation of Pinus caribaea var. Hondurensis. The experiment was installed on the campus of the Faculty of Engineering of Ilha Solteira (Unesp), located in Selviria, state of Mato Grosso do Sul, Brazil, in a RED OXYSOL Dystroferric, very clayey texture. The following soil chemical attributes were analyzed: phosphorus (P), organic matter (OM), hydrogen ionic potential (pH), potassium (K), calcium (Ca), magnesium (Mg), potential acidity (C), base saturation (V%), calcium (CaT), magnesium (MgT) and aluminum (m) in CEC (Cationic Exchange Capacity). All soil and plant attributes presented simple spatial dependence in the studied area, except for height, diameter at breast height and potential acidity in the 0.10-0.20 m layer, evidencing that Pinus management can be performed according to the specific site in the conditions of the study. Potassium was the soil attribute that best correlated with the productivity of Pinus in volume, as well as the best indicators for the estimation of productivity.
Keywords: Soil chemistry; Kriging; Forestry; Variability